Sosialisasi Hukum Tentang Pengaturan Kewenangan Pengelolaan Wilayah Pesisir - Hanafi, Irma Halimah; Riry, Welly Angela (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: Coastal areas are areas where land and sea meet, towards land, coastal areas include parts of land, both dry and submerged in water, which are still influenced by sea properties such as tides, sea breezes and the expansion of salt water towards the sea, including parts of the sea that it is still influenced by natural processes that occur on land such as sedimentation and fresh water flows. Management of coastal areas and small islands is carried out through coordinating planning, utilization, supervision and control of coastal and small island resources carried out by the government and regional governments, between land and marine ecosystem sectors, as well as between science and management to improve people's welfare. In this regard, the authority to manage coastal areas is regulated in several statutory regulations which can cause problems regarding which institution has the authority to manage coastal areas, especially in Ambon Bay.Purposes of Devotion: The aim of this community service activity (PKM) is to ensure that the Ambon Bay coastal community, especially the community in Wayame Village, understands the authority of institutions in regulating coastal area management and also to obtain suggestions and input from coastal communities directly which can become study material for the Government. Method of Devotion: Activities are carried out in the form of outreach to the community with the stages of implementing community service in outline starting from: (1) Preliminary Data Collection; (2) Community Service Activities take the form of socialization; (3) Evaluation of Community Service activities.Results of the Devotion: The lack of public understanding regarding the role and function of institutional management of the Ambon Bay coastal area means that it needs to be reviewed so that its duties and roles in carrying out, improving the social and economic life of the community, especially those who live around the Ambon Bay coastal area, can increase. To improve the standard of living of coastal communities, an empowerment program can be launched for fishermen who are the main source of livelihood for communities in coastal areas. Empowerment is carried out through developing alternative livelihoods, increasing access to capital for fishermen, increasing access to technology, both fishing/cultivation technology and processing of fishery products, facilitating fishermen to obtain a decent market.